Evaluation of Facility Services at Kepatang Train Station Based on User and Community Interest - Ahmad Soimun; Wahyu Johnata (Politeknik Perkeretaapian Indonesia Madiun, 2023)
This study aims to evaluate the service infrastructure of Ketapang Railway Station based on users and public interest. The research method used was a survey method by distributing questionnaires to Ketapang railway station users and potential users of the station. The questionnaire included questions about the quality of station services, user expectations and needs, as well as public interest in railway station services. The results of the study showed that the infrastructure facilities at Ketapang railway station had met the minimum standard service regulations in place. From the analysis of the customer satisfaction index, it was found that the criteria for